You are on page 1of 43

Laplace Transform Methods and

Solution of Differential equation

The Laplace transform was developed by


the French mathematician by the same
name (1749-1827) and was widely
adapted to engineering problems in the
last century. Its utility lies in the ability to
convert differential equations to algebraic
forms that are more easily solved. The
notation has become very common in
certain areas as a form of engineering
“language” for dealing with systems.
1
Differential Equation

Steps involved
in using the Transform differential
equation to

Laplace algebraic equation.

transform.

Solve equation
by algebra.

Determine
inverse
transform.

Solution

2
Laplace Transformation

L[ f (t )] = F ( s )
−1
L [ F ( s)] = f (t )

F ( s ) = ∫ f (t )e dt
− st
0

3
Basic Theorems of Linearity
L[ Kf (t )] = KL[ f (t )] = KF ( s )
L[ f1 (t ) + f 2 (t )] = L[ f1 (t )] + L[ f 2 (t )]
= F1 ( s ) + F2 ( s )
The Laplace transform of a product is
not the product of the transforms.

L[ f1 (t ) f 2 (t )] ≠ F1 ( s ) F2 ( s )
4
Figure 2. Illustration of the unit step
function.
u (t )

0 t

5
Example 1. Derive the Laplace
transform of the unit step function.

F ( s ) = ∫ (1)e dt
− st
0


e 
− st
e  1 −0
F ( s) =  = 0− =
−s  0  −s  s

6
Example 2. Derive the Laplace
transform of the exponential function
−α t
f (t ) = e
∞ ∞
F ( s) = ∫ e e dt = ∫ e
−α t − st −( α + s ) t
dt
0 0

e 
− ( s +α ) t
e −0
=  =0−
−( s + α )  0 −( s + α )
1
=
s +α
7
Table 10-1. Common transform pairs.
f (t ) F (s) =
L[ f (t )]
1 or u (t ) 1 T-1
s
α T-2
e−t
1
s+ α
sin ω
t ω T-3
s2 ω
+2

cos ω
t s T-4
s2 + ω
2

α
e−t
sin ω
t ω T-5*
α
(s +

) 2 2

α
e−t
cos ω
t s+ α T-6*
α
(s +

) 2 2

t 1 T-7
s2
tn n! T-8
s n+1

α T-9
e−t n
t n!
(s + α )n+
1

δ
(t ) 1 T-10

*Use when roots are complex.


8
Example 3. A force in newtons (N) is
given below. Determine the Laplace
transform.

f (t ) = 50u (t )
50
F (s) =
s

9
Example 4. A voltage in volts (V)
starting at t = 0 is given below.
Determine the Laplace transform.
−2 t
v(t ) = 5e sin 4t
4
V ( s ) = L[v(t )] = 5 ⋅
( s + 2) + (4)
2 2

20 20
= 2 = 2
s + 4 s + 4 + 16 s + 4 s + 20
10
Example 5. A pressure in pascals (p)
starting at t = 0 is given below.
Determine the Laplace transform.
−4 t
p (t ) = 5cos 2t + 3e
s 1
P ( s ) = L[ p (t )] = 5 ⋅ 2 + 3⋅
s + (2) 2
s+4
5s 3
= 2 +
s +4 s+4
11
Inverse Laplace Transforms
by Identification
When a differential equation is solved by
Laplace transforms, the solution is
obtained as a function of the variable s.
The inverse transform must be formed in
order to determine the time response.
The simplest forms are those that can be
recognized within the tables and a few of
those will now be considered.

12
Example 6. Determine the inverse
transform of the function below.

5 12 8
F (s) = + 2 +
s s s +3
−3t
f (t ) = 5 + 12t + 8e

13
Example 7. Determine the inverse
transform of the function below.
200
V (s) = 2
s + 100
 10 
V ( s ) = 20  2 2 
 s + (10) 

v(t ) = 20sin10t
14
Example 8. Determine the inverse
transform of the function below.
8s + 4
V (s) = 2
s + 6s + 13
When the denominator contains a
quadratic, check the roots. If they are
real, a partial fraction expansion will be
required. If they are complex, the table
may be used. In this case, the roots are

s1,2 = −3 ± 2i
15
Example 8. Continuation.

s + 6 s + 13
2

= s + 6 s + (3) + 13 − (3)
2 2 2

= s + 6s + 9 + 4
2

= ( s + 3) + (2)
2 2

16
Example 8. Continuation.

8( s + 3) 4 − 24
V (s) = +
( s + 3) + (2) ( s + 3) + (2)
2 2 2 2

8( s + 3) 10(2)
= −
( s + 3) + (2) ( s + 3) + (2)
2 2 2 2

−3t −3t
v(t ) = 8e cos 2t − 10e sin 2t
17
Forms for CCLODE Transforms
N ( s)
F ( s) =
D( s)
n −1
N ( s ) = an s + an −1s
n
+ ... + a1s + a 0
m −1
D( s ) = bm s + bm −1s
m
+ ... + b1s + b0
N (s)
F (s) =
bm ( s − p1 )( s − p2 )....( s − pm )
18
The roots of D(s) are called poles and
they may be classified in four ways.
1. Real poles of first order.
2. Complex poles of first order (including
purely imaginary poles)
3. Real poles of multiple order
4. Complex poles of multiple order
(including purely imaginary poles)

19
Partial Fraction Expansion
Real Poles of First Order

A1 A2 Ar
F (s) = + + .... + + R(s)
s − p1 s − p2 s − pr
Ak = ( s − pk ) F ( s ) ] s = p
k

f1 (t ) = A1e p1t
+ A2e p2 t
+ .... Are p rt

20
Example 9. Determine inverse
transform of function below.
s+6 s+6
F ( s) = 2 =
s + 3s + 2 ( s + 1)( s + 2)
s+6 A1 A2
F (s) = = +
( s + 1)( s + 2) s + 1 s + 2
s + 6 −1 + 6
A1 = ( s + 1) F ( s ) ] s =−1 = = = 5
s + 2  s =−1 −1 + 2
21
Example 10. Continuation.

s + 6 −2 + 6
A2 = ( s + 2) F ( s ) ] s =−2 = = = − 4
s + 1  s =−2 −2 + 1
5 4
F (s) = −
s +1 s + 2
−t −2 t
f (t ) = 5e − 4e
22
Example 11. Determine
exponential portion of inverse
transform of function below.

50( s + 3)
F (s) =
( s + 1)( s + 2)( s + 2 s + 5)
2

A1 A2
F1 ( s ) = +
s +1 s + 2

23
Example 11. Continuation.

50( s + 3)  (50)(2)
A1 =  = = 25
( s + 2)( s + 2 s + 5)  s =−1 (1)(4)
2

50( s + 3)  (50)(1)
A2 =  = = −10
( s + 1)( s + 2 s + 5)  s =−2 (−1)(5)
2

−t − 2t
f1 (t ) = 25e − 10e
24
Partial Fraction Expansion for
First-Order Complex Poles

( s + bs + c) ⇒ p1,2 = − α ± iω
2

As + B
F (s) = 2 + R(s)
s + bs + c

25
Example 12. Complete the inverse
transform of Example 10.
50( s + 3) 25 10 As + B
= − + 2
( s + 1)( s + 2)( s + 2 s + 5) s + 1 s + 2 s + 2s + 5
2

50(3) 25 10 B B = −25
= − +
(1)(2)(5) 1 2 5
50(4) 25 10 A + B A = −15
= − +
(2)(3)(8) 2 3 8
25 10 −15 s − 25
F ( s) = − + 2
s + 1 s + 2 s + 2s + 5 26
Example 11. Continuation.
−15s − 25
F2 ( s ) = 2
s + 2s + 5
s + 2s + 5 = s + 2s + 1 + 5 − 1 = ( s + 1) + (2)
2 2 2 2

−15s − 25 −15( s + 1) −5(2)


F2 ( s ) = = +
( s + 1) + (2)
2 2
( s + 1) + (2) ( s + 1) 2 + (2) 2
2 2

f (t ) = f1 (t ) + f 2 (t )
−t − 2t −t −t
= 25e − 10e − 15e cos 2t − 5e sin 2t
27
Second-Order Real Poles
Assume that F(s) contains a denominator
factor of the form (s+α )2. The expansion
will take the form shown below.

C1 C2
F (s) = + + R(s)
(s + α ) s + α
2

C1 = (s + α ) 2 F (s ) 
s =−α

−α t −α t −α t
f1 (t ) = C1te + C2 e = (C1t + C2 )e
28
Example 12. Determine inverse
transform of function below.
60
F (s) =
s ( s + 2) 2

60 A C1 C2
F (s) = = + +
s ( s + 2) 2
s ( s + 2) ( s + 2)
2

60  60
A = sF ( s) ] s =0 = 2
= = 15
( s + 2)  s =0 (0 + 2) 2

60  60
C1 = ( s + 2) F ( s ) 
2
=  = = − 30
s =−2 s  s =−2 −2
29
Example 12. Continuation.
60 15 30 C2
F ( s) = = − +
s ( s + 2) 2
s ( s + 2) s + 2
2

60 15 30 C2 C2 = −15
= − +
(1)(1 + 2) 2
1 (1 + 2) (1 + 2)
2

60 15 30 15
F ( s) = = − −
s ( s + 2) 2
s ( s + 2) s + 2
2

−2 t −2 t −2 t
f (t ) = 15 − 30te − 15e = 15 − 15e (1 + 2t )
30
Laplace Transform Operations

f (t ) F (s)
f '(t ) sF ( s ) −f (0) O-1
t
F (s) O-2

f (t )dt

α
0
s
e−α t
f (t ) F (s + ) O-3

f (t − −T )u (t T ) e−sT
F (s) O-4

f (0) lim sF ( s) O-5


s→

lim f (t ) lim sF ( s )* O-6


t→
∞ s→
0

*Poles of sF ( s ) must have negative real parts.

31
Significant Operations for Solving
Differential Equations

L[ f '(t )] = sF ( s ) − f (0)
L[ f "(t )] = s F ( s ) − sf (0) − f '(0)
2

 t
 F (s)
L ∫ f (t )dt =
 0  s
32
Procedure for Solving DEs
d2y dy
b2 2 + b1 + b0 y = f (t )
dt dt
 d2y dy 
L b2 2 + b1 + b0 y  = L [ f (t ) ]
 dt dt 
b2  s 2Y ( s ) − sy (0) − y '(0) 
+b1 [ sY ( s ) − y (0) ] + b0Y ( s ) = F ( s )

F (s) sb2 y (0) + b2 y '(0) + b1 y (0)


Y (s) = +
b2 s + b1s + b0
2
b2 s + b1s + b0
2

33
Example 13. Solve DE shown below.
dy
+ 2 y = 12 y (0) = 10
dt
 dy 
L   + 2 L [ y ] = L [ 12 ]
 dt 
12
sY ( s ) − 10 + 2Y ( s ) =
s
12
( s + 2 ) Y (s) = 10 +
s
10 12
Y ( s) = +
s + 2 s ( s + 2)
34
Example 13. Continuation.
12 A1 A2
= +
s ( s + 2) s s + 2
 12   12 
A1 = s   =  =6
 s ( s + 2)  s =0  s + 2  s =0
 12   12 
A2 = ( s + 2)   =  = −6
 s ( s + 2)  s =−2  s  s =−2

10 6 6 6 4
Y ( s) = + − = +
s+2 s s+2 s s+ 2
−2 t
y (t ) = 6 + 4e
35
Example 14. Solve DE shown below.
dy
+ 2 y = 12sin 4t y (0) = 10
dt
12(4)
sY ( s ) − 10 + 2Y ( s ) = 2
s + 16
10 48
Y (s) = +
s + 2 ( s + 2)( s + 16)
2

48 A B1s + B2
= + 2
( s + 2)( s + 16) s + 2 s + 16
2

36
Example 14. Continuation.
48  48
A= 2  = = 2.4
s + 16  s =−2 20
48 2.4 B1s + B2
= + 2
( s + 2)( s + 16) s + 2 s + 16
2

48 2.4 B2
= + B2 = 4.8
(2)(16) 2 16

48 2.4 − B1 + B2 B1 = −2.4
= +
(1)(17) 1 17
37
Example 14. Continuation.

10 2.4 2.4 s 4.8


Y (s) = + − 2 + 2
s + 2 s + 2 s + 16 s + 16

−2 t
y (t ) = 12.4e − 2.4 cos 4t + 1.2sin 4t

38
Example 15. Solve DE shown below.
2
d y dy
2
+ 3 + 2 y = 24
dt dt
y (0) = 10 and y '(0) = 0
24
s Y ( s ) − 10s − 0 + 3 [ sY (s ) − 10 ] + 2Y ( s ) =
2

s
24 10 s + 30
Y (s) = + 2
s ( s + 3s + 2) s + 3s + 2
2

24 10 s + 30
= +
s ( s + 1)( s + 2) ( s + 1)( s + 2)
39
Example 15. Continuation.
24 12 24 12
= − +
s ( s + 1)( s + 2) s s + 1 s + 2
10s + 30 20 10
= −
( s + 1)( s + 2) s + 1 s + 2
12 4 2
F ( s) = − +
s s +1 s + 2
−t −2 t
f (t ) = 12 − 4e + 2e
40
Example 16. Solve DE shown below.
d2y dy
2
+ 2 + 5 y = 20
dt dt
y (0) = 0 and y '(0) = 10
20
s Y ( s ) − 0 − 10 + 2 [ sY (s ) − 0 ] + 5Y (s ) =
2

s
20 10
Y ( s) = + 2
s ( s + 2 s + 5) s + 2 s + 5
2

41
Example 16. Continuation.
20 4 As + B
= + 2
s ( s + 2 s + 5) s ( s + 2s + 5)
2

20 4 A+ B
= +
(1)(1 + 2 + 5) 1 (1 + 2 + 5)
20 4 −A + B
= +
(−1)(1 − 2 + 5) −1 (1 − 2 + 5)

A = −4 B = −8
42
Example 16. Continuation.

4 −4 s − 8 10 4 −4s + 2
Y ( s) = + 2 + 2 = + 2
s s + 2s + 5 s + 2s + 5 s s + 2s + 5

s + 2 s + 5 = s + 2 s + 1 + 5 − 1 = ( s + 1) + (2)
2 2 2 2

4 −4( s + 1) 3(2)
Y (s) = + +
s ( s + 1) + (2) ( s + 1) 2 + (2) 2
2 2

−t −t
y (t ) = 4 − 4e cos 2t + 3e sin 2t
43